PENYUSUNAN LAPORAN KEUANGAN BERBASIS SAK EMKM PADA UMKM KARYA INDAH - Rianto, Panji; Ardiani, Susi; Dwitayanti, Yevi (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2024)
The aim of preparing this report is to understand and prepare financial reports based on SAK EMKM for UMKM Karya Indah. Data collection technique used interview data, documentation and observations obtained from the company. Based on data obtained from UMKM Karya Indah, which operates in the sales of building materials, there are not all records of transactions that occur and they have not prepared financial reports. Therefore, the things discussed in this report are analyzing financial reporting problems at UMKM Karya Indah, the author proposes an accounting recording procedure in stages starting from compiling account codes, analyzing every transaction that occurred from January to March 2023 then making a journal and completing it. stages of the accounting cycle to produce financial reports using Microsoft Excel which can help make calculations more efficient and automatically calculate data. These financial reports are in the form of financial position reports, profit and loss reports, and notes to financial reports. Keywords: SAK EMKM, Financial Statements